Green superabsorbent hydrogel derived from activated charcoal and glycerol with maleic acid as a cross-linker - Kasimu, Titus M.; Mbuvi, Harun M.; Maingi, Francis M. (Journal of Experimental Sciences, 2024)
Superabsorbent hydrogels characterize a set of polymeric materials with three-dimensional structures capable of absorbing large amounts of water due to their hydrophilic functional groups on their surface. Their application in industries, agriculture, and the environment is of primary significance. This study reports the synthesis and characterization of green superabsorbent hydrogels derived from activated charcoal. The process involved a polymerization reaction between activated charcoal (AC) with glycerol (G) using sodium hydroxide as an initiator in the absence and presence of maleic acid as a crosslinker to synthesize HCG-1 and HCG-2 superabsorbent hydrogel respectively. Characterization of the hydrogels was done using Fourier transform infrared (FT-IR) spectroscopy, scanning electron microscope (SEM), and X-ray diffraction (XRD). Optimization conditions were done by synthesizing hydrogel with varying dosages of both activated carbon and maleic acid as well as swelling time. The FT-IR results showed the appearance of strong sharp peaks at 1591.34 cm-1 and 1400.28 cm-1 in HCG-1 associated with -COO¯ symmetric stretching and asymmetric bending vibrations, indicating interlink between reacting monomers. A new absorption band at 1639.48 cm-1 associated with -COO¯ bending in non-conjugated ester indicates ester-crosslink in HCG-2 hydrogel. XRD analysis showed a phase shift from semi-crystalline to crystalline structure upon crosslinking. SEM analysis showed a crystalline intact, rigid structure without voids and pores on its surface in HCG-1 compared to the smooth irregular pores and lamina structure observed in HCG-2 hydrogel. The dosage ratio of AC: G: maleic acid of 8:5:1 produced hydrogel with an optimal water absorption capacity of 1255.80±0.70%. Maleic acid was found to improve the water absorption capacity of the superabsorbent. The study is an eye opener towards the application of biodegradable hydrogels in agriculture, especially in semi and arid regions.